Correlation Of Social Interaction With Loneliness Levels Among The Elderly at the Elderly Community Health at Samarinda - Veriyallia, Vera; Tubulus, Etza Novela; Ghofar Abdulloh, Ahmad Abdul; Ain, Anisa; Layun Rining, Marina Kristi; Utami, Rinda Aulia (Fakultas Kedokteran, 2026)
Introduction: The elderly population is characterized by significant physical, psychological, and social changes. Loneliness is one of the most common psychosocial problems experienced by older adults. Low levels of social interaction can increase the risk of loneliness in this population. Conversely, good social interaction plays a vital role in maintaining mental health and enhancing the quality of life among the elderly. Objective: This study aimed to determine the correlation between social interaction and loneliness levels among the elderly attending the Elderly Posyandu at Sidomulyo Public Health Center, Samarinda City. Methods: This quantitative study employed a cross-sectional design. The sample consisted of 101 respondents, determined using the Slovin formula and selected through consecutive sampling. Data were collected using a validated social interaction questionnaire and the UCLA Loneliness Scale, both of which had been tested for reliability and validity. Data were analyzed using Kendall's Tau-C correlation test. Results: The findings revealed a significant correlation between social interaction and loneliness levels among the elderly (p = 0.000, p < 0.05), with a correlation coefficient of r = -0.603. This value indicates a strong negative correlation, meaning that higher levels of social interaction are associated with lower levels of loneliness among older adults. Conclusion: Better social interaction among the elderly is associated with lower levels of loneliness. These findings underscore the important role of social interaction in reducing loneliness in the elderly population.